Employment and Growth Effects of Tax Reforms - Jochen Michaelis; Angela Birk (Hamburg Institute of International Economics (HWWA), 2004)
This paper explores how revenue-neutral tax reforms impact employment and economic growth in a model of endogenous growth and search frictions on the labor market. We analyze how savings and the incentive to create new jobs are affected by tax swaps between wage income taxes, payroll taxes, capital income taxes and taxes levied on capital costs. In our framework, the payroll tax is found to be neutral. If this tax is used to finance a cut in the capital income tax, we will observe an increase in both growth and, via the capitalization effect, employment. Most other tax reforms, however, imply a trade-off between employment and growth.
Keywords: O4; J6; H2; E6; 330; search unemployment; growth; tax reform; Steuerreform; Neue Wachstumstheorie; Arbeitsuche; Friktionelle Arbeitslosigkeit; Beschäftigungseffekt; Theorie